Clinical outcomes and inflammatory response to single‐incision laparoscopic (SIL) colorectal surgery: a single‐blinded randomized controlled pilot study. (13th October 2018) - Borowski, D. W.; Baker, E. A.; Wilson, D.; Garg, D. K.; Gill, T. S.
Abstract: Aim: Single‐incision laparoscopic (SIL) surgery is expanding, but its benefits, efficacy and safety compared with conventional laparoscopic (CL) surgery remain unclear. This pilot study examined clinical outcomes and biochemical markers of inflammation for colorectal resections by SIL and CL in a randomized controlled pilot trial. Method: Fifty patients undergoing elective colorectal resection were randomized to either SIL or CL. Primary outcomes were operating time and length of stay (LoS); secondary outcomes included combined length of scars, pain scores, complications, Quality of Life EQ5D‐VAS and the inflammatory markers interleukin‐6 (IL‐6), IL‐8 and C‐reactive protein (CRP) at baseline, 2, 6, 24 and 72 h. Results: There was no difference in age, gender, body mass index, indications and site of surgery, American Society of Anesthesiologists grade or incidence of previous surgery between the groups. Except for one conversion from SIL to open surgery, surgery was completed as intended. No difference between SIL and CL was found for operating time [median 130 (72–220) vs 130 (90–317) min, respectively, P  = 0.528], LoS [median 4 (3–8) vs 4 (2–19)days, P  = 0.888] and time to first flatus [2 (1–4) vs 2 (1–5) days, P  = 0.374]. The combined length of scars was significantly shorter for SIL [4 (2–18) vs 7 (5–8) cm, P  < 0.001]; in each group, four postoperative complications occurred (16%). Postoperative pain scores were similar [mean 7.67 (interquartile range 4) vs 7.25 (interquartile range 3.75), P  = 0.835] to day 3. EQ5D‐VAS was no different for both groups at discharge [72.5 (40–90) vs 70 (30–100), P  = 0.673] but slightly higher for CL at 3 months [79 (45–100) vs 90 (50–100), P  = 0.033].The IL‐6, IL‐8 and CRP levels between both groups showed similar peaks and no significant differences. Conclusion: SIL colorectal surgery by experienced laparoscopic surgeons appears to be safe and equivalent to CL, with no discernible difference in its effect on the physiological response to surgical trauma.